Literature Review Study of Google Scholar Indexed Articles on Mycorrhiza in Plant Disease Control - Parwito, Parwito; Guswarni Anwar (Asosiasi Mikoriza Indonesia, 2024)
Mycorrhiza is a fungus that is symbiotic with plant roots, has great potential in biological control of plant diseases. The purpose of this literature review study is to examine in depth the role of mycorrhiza in plant disease control based on scientific articles indexed on Google Scholar. This study used the Systematic Literature Review (SLR) method to collect data from 100 relevant scientific articles, indexed on Google Scholar, with a range of years 2010-2024. The data was analyzed using VOSviewer software to map the relationship between keywords. The results of network, overlay and density visualization using VOSviewer showed that mycorrhiza, particularly arbuscular mycorrhizal fungi (AMF), have a central role in plant disease control through symbiotic interactions with roots and soil microorganisms. The network visualization highlights the close relationship between keywords such as